2013
DOI: 10.2139/ssrn.2321726
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Human Resource Management Practices for a Firm's Innovation Performance

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…These scholars interpreted this result as evidence of complementarities between HRM practices and innovation. Arvanitis et al (2013) find cumulative effects from the use of HRM practices on innovation. From a certain threshold on, the effect on innovation is larger with the firm's introduction and intensive use of larger numbers of individual HRM practices.…”
Section: Management Literaturementioning
confidence: 96%
See 3 more Smart Citations
“…These scholars interpreted this result as evidence of complementarities between HRM practices and innovation. Arvanitis et al (2013) find cumulative effects from the use of HRM practices on innovation. From a certain threshold on, the effect on innovation is larger with the firm's introduction and intensive use of larger numbers of individual HRM practices.…”
Section: Management Literaturementioning
confidence: 96%
“…They found correlation between innovation and the factors under examination, but in many cases this was weak. Many empirical studies find different innovation results according to the type of management practice under examination: Zhou et al (2011) for the Netherlands, Cosh et al (2012) for UK, Chang et al (2012) for Taiwanese firms, Jiang et al (2012) for Chinese firms, Koski et al (2012) for Finnish manufacturing firms, and Arvanitis et al (2013) for Swiss and Greek firms.…”
Section: Management Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Van Reenen (2007, 2010) found that measures of monitoring, targetsetting and incentivizing, as assessed via surveys, are strongly associated with productivity and other measures of firm-level performance. The question of whether there is impact from management practices precisely in the area of innovation has received less attention, although several scholars have recently explored the effects from firm organization and employment conditions on propensity to innovate and on actual success in innovation (generally represented by sales of innovative products) (Arvanitis et al 2013). 4 Other scholars have attempted to examine managerial effects on innovation by examining mainly human resources management (HRM) practices, such as employee training, hiring criteria, teamwork, job design and employee hierarchies (Ichniowski and Shaw 2003).…”
Section: Management Literaturementioning
confidence: 99%